X-ray based methods for non-destructive testing and material characterization - Hanke, Randolf; Fuchs, Theobald; Uhlmann, Norman (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2008)
The increasing complexity and miniaturization in the field of new materials as well as in micro-production requires in the same way improvements and technical advances in the field of micro-NDT to provide better quality data and more detailed knowledge about the internal structures of micro-components. Therefore, non-destructive methods like radioscopy, ultrasound, optical or thermal imaging increasingly gain in importance with respect to ongoing product and material development in the different phases like material characterization, production control or module reliability testing. Because of the manifold different application fields, i.e., certain physical NDT methods applied to material inspection, characterization or reliability testing, this contribution will focus on the radioscopic-based methods related to their most important applications. Today, in modern industrial quality control, X-ray transmission is used in two different ways: • Two-dimensional radioscopic transmission imaging (projection technique), usually applied to inline inspection tasks in application fields like lightweight material production, electronic component soldering or food production. • Computed tomography (CT) for generation of three-dimensional data, representing spatial information and density distribution of objects. CT application fields are on the one hand the understanding of production process failure or component and module inspection (completeness) and on the other hand the dimensional measuring of hidden geometrical outlines (metrology). This paper demonstrates the methods including technical set-ups (X-ray source and detector), imaging and reconstruction results and the methods for high speed and high-resolution volume data generation and evaluation.
EAM Import::2019-03-12